FINANCE AND ACCOUNTING (MISCELLANEOUS) IN UZBEKISTAN: CURRENT TRENDS AND CHALLENGES - Isakov Ilham Janabay ugli (Ecominds Press, 2025)
This paper provides a comprehensive analysis of the current state of business, management, and accounting in Uzbekistan, emphasizing the impact of recent economic reforms, regulatory changes, and emerging challenges. The study utilizes a mixed-methods approach, combining statistical analysis of key economic indicators with qualitative insights from expert interviews. The findings reveal notable advancements in financial transparency, corporate governance, and the overall business environment due to government initiatives aimed at improving investment attractiveness and economic liberalization. However, several critical challenges remain, including bureaucratic inefficiencies, regulatory inconsistencies, and the slow pace of digital transformation in financial and managerial sectors. Moreover, the research highlights the growing role of foreign direct investment (FDI) and public-private partnerships (PPPs) in shaping Uzbekistan’s economic landscape. The study also examines the evolving role of accounting standards, tax reforms, and financial reporting practices in aligning the country with international business norms. Based on the analysis, the paper provides policy recommendations to strengthen economic resilience and enhance Uzbekistan’s global competitiveness. These include streamlining administrative procedures, accelerating digitalization in business operations, and fostering a more robust regulatory environment to support sustainable economic growth.
Keywords: Uzbekistan, business environment, management, accounting, economic reforms, financial transparency, corporate governance, foreign direct investment (FDI), digital transformation, regulatory framework.